TQM : a case study of Malaysia Airlines Academy / Kamal Kishore Jain - Jain, Kamal Kishore (Faculty of Business and Management ; UiTM Press, 2000)
Malaysia Airlines, with almost 40 domestic and over 80 foreign destinations, is the largest passenger airline in Southeast Asia. At its very is the people and their dedication and commitment to upholding the golden reputation of Malaysia Airlines. The shaping force behind its people is the Malaysia Airlines Academy - MAA. The Academy is a Training Institution approved as a training provider by the Human Resources Development Council (HRDC); the Ministry of Culture, Arts and Tourism (MOCAT), and the Ministry of Education of Malaysia. Being an approved training provider the Academy must ensure that its products and services meet customer requirements, and Safety Training modules meet statutory requirements of Department of Civil Aviation.